2015
DOI: 10.1186/s13018-015-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of iatrogenic foraminal stenosis from lordotic correction in the development of C5 palsy after posterior laminectomy and fusion

Abstract: BackgroundPost-operative C5 nerve root palsy is a known complication following cervical spine surgery. Although several theories have been proposed, there remains no consensus as to the etiology of the palsies. Multiple pre-operative radiographic measures have been assessed for utility in predicting palsy. The purpose of this study is to evaluate published radiographic parameters as well as specifically evaluate the effect of cervical lordosis in the development of C5 palsy to establish thresholds that reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 35 publications
0
34
1
Order By: Relevance
“…In three reviews focused on AS patients, the sample sizes were 188-286, 19-23% of patients had neurologic complications mostly in the form of a transient C8-radiculopathy, and 3-4% had permanent spinal cord deficits. Kurakawa [70], Nakashima [71], Hojo [72] and Blizzard [73] reported an increased rate of C5-palsy with increasing CK-correction without preventive foraminotomy. In a series of 16 patients that underwent circumferential release and 3CO, 19% had postop temporary C5-palsy [34].…”
Section: Complicationsmentioning
confidence: 98%
“…In three reviews focused on AS patients, the sample sizes were 188-286, 19-23% of patients had neurologic complications mostly in the form of a transient C8-radiculopathy, and 3-4% had permanent spinal cord deficits. Kurakawa [70], Nakashima [71], Hojo [72] and Blizzard [73] reported an increased rate of C5-palsy with increasing CK-correction without preventive foraminotomy. In a series of 16 patients that underwent circumferential release and 3CO, 19% had postop temporary C5-palsy [34].…”
Section: Complicationsmentioning
confidence: 98%
“…They display an overall postoperative palsy rate of 10.9%. Although a rate up to 24% can be observed, most studies reported similar numbers[ 7 , 22 ]. However, most of these studies are not comparable to each other.…”
Section: Discussionmentioning
confidence: 99%
“…In order to minimize the risk of C5 nerve root stress due to spinal cord shift, additional decompression of the neuroforamen can be considered. Several studies demonstrate that preoperative anteroposterior diameter of the neuroforamen was found to be significantly smaller in patients with C5 palsy[ 7 , 11 , 25 ]. As a consequence, when a wide decompression, which includes more than one level or a corpectomy with potential excessive shifting of the spinal cord is required, prophylactic foraminotomy at the level C4/5 might reduce C5 nerve root palsy, as we performed in all of our procedures in which the segment C4/5 was involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…believed that the increase of postoperative cervical lordosis was negatively correlated with the severity of axial pain, especially for lordosis greater than 20°. While the increased cervical lordosis would promote the backward drift of the spinal cord, and further increase the tension of C5 nerves, leading to the occurrence of C5 palsy [20]. For this contradiction, since the balance point of cervical curvature is di cult to select, it is di cult for spine surgeons to balance the occurrence of AS and C5 palsy by controlling the cervical curvature.…”
Section: Discussionmentioning
confidence: 99%